Analysis of Clearance-In and Clearance-Out Procedures for Local Bulk Carrier Vessels at PT Pelayaran Faputra Samudera, Morowali Branch - Yatinde, Haryadi; Setiono, Beni Agus; Purwiyanto, Didik (Universitas Hang Tuah, 2026)
Local bulk carrier vessels require well-organized clearance in and clearance out procedures to ensure smooth port operations. At PT. Pelayaran Faputra Samudera Morowali Branch, delays in information and document submission, changes in vessel schedules, and disruptions to electronic service systems were still encountered. This study analyzes the procedures for handling clearance in and clearance out and identifies the obstacles in serving local bulk carrier vessels. A descriptive qualitative field approach was employed. Data were collected through observation, semi-structured interviews with three informants consisting of the Branch Manager and two Operational Staff, and documentation. Data were analyzed through data condensation, data display, and conclusion drawing and verification. The findings show that the procedures have been implemented in accordance with the company Standard Operating Procedures through document verification, service submission using Inaportnet and SIMKARKES, verification, coordination with relevant agencies, and issuance of the Sailing Approval Letter. Obstacles included document delays, changes in vessel schedules, weather conditions, and system disruptions. The findings imply that timely information and effective coordination are essential to improve vessel clearance service effectiveness.